Arduino-based devices in healthcare and environmental monitoring - Nkgaphe T. Tsebesebe; Kelvin Mpofu; Sudesh Sivarasu; Patience Mthunzi-Kufa (Discover Internet of Things)
Abstract Rapid increases in diseases and pandemics over the past years have led to the development of more affordable and accessible biosensing equipment, especially in underdeveloped regions. One of the open-source hardware that has the potential to develop advanced health equipment is the Arduino platform. This review emphasizes the importance of open-source technology, specifically the Atmel family of microcontrollers used in the Arduino development board, and the applications of the Arduino platform in biosensing technologies to advance PoC devices. Furthermore, the review highlights the use of machine learning algorithms to enhance the functionality of user-defined prototypes, aiming to realize PoC devices. It also addresses the successes and limitations of microcontrollers and machine learning in the development of PoC devices using open-source technology. The primary purpose of this paper is to investigate how the Arduino platform can be leveraged to create effective and affordable biosensing solutions, by examining the integration of Arduino with various types of biosensors. The review showcases the potential of Arduino to democratize and innovate biosensor technology. Lastly, this paper extends the investigation of applications of Arduino to general health care and environmental monitoring.